Air pollution increases gastroesophageal reflux disease risk: evidence from a prospective cohort study - Yan Ran; Jian Lei; Lianli Wang; Laifu Li; Fangchen Ye; Lin Mei; Zhuoya Sun; Jiamiao Chen; Fei Dai (Frontiers in Public Health)
BackgroundGastroesophageal reflux disease (GERD) is one of the most prevalent gastrointestinal disorders with uncertain etiology and high prevalence. Ambient air pollution has been linked to gastrointestinal diseases, but the impact of long-term air pollution exposure on GERD incidence is still unclear.MethodsWe performed a cohort study using the UK Biobank database. Annual mean concentrations of air pollutants, including PM10, PM2.5–10, PM2.5, NOX, and NO2, were obtained from the ESCAPE study using the land use regression model. The Cox proportional hazard regression model was employed to estimate the percentage change of GERD incidence risk related to long-term air pollutant exposures. We further explored the exposure-response relationship curves and identified the vulnerable populations.ResultsDuring a follow-up period of 14.1 ± 2.4 years, a total of 32,413 (11.2%) individuals were diagnosed with GERD among 289,387 participants. We estimated that each interquartile range increase in PM10, PM2.5–10, PM2.5, NOX, NO2, and NO was associated with 1.69, 1.29, 3.57, 2.08, 1.93, and 2.28% higher incidence risks of GERD, respectively. Almost linear exposure-response curves were observed, particularly for GERD without esophagitis. The females, middle-aged, overweight, White ethnicity, and higher socioeconomic status individuals were more vulnerable to GERD when exposed to air pollutants.ConclusionThis study provided robust evidence supporting the association between long-term exposure to air pollutants and increased risk of GERD incidence. Our research revealed that exposure to both particulate matter and gaseous pollutants was associated with a higher risk of GERD, especially for GERD without esophagitis.